Development of the muscle dysmorphia inventory (MDI) - Rhea, D. J.; Lantz, C. D.; Cornelius, A. E. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The development of the 6-factor, 27-item Muscle Dysmorphia Inventory (MDI) was based on Lantz et al. proposed model of characteristics associated with Muscle Dysmorphia. METHODS: Experimental design: quantitative procedures including item-to-total correlations, exploratory and confirmatory factor analyses, and structure equation modeling confirmed the construct validity of the scale. Convergent validity was also tested. Setting: bodybuilding and powerlifting competition venues, weight training facilities, and university athletic venues. Participants: the 1(st) study consisted of 77 experienced male free weight lifters. The 2(nd) study consisted of 156 male non-competitive bodybuilders and weight lifters and 168 elite level powerlifters and bodybuilders. The 3(rd) study consisted of 151 male and female bodybuilders and weight lifters. Measures: each participant completed demographic information, the MDI, Drive for Thinness subscale of the Eating Disorder Inventory, and the Training Dependency subscale of the Bodybuilding Dependence Scale. RESULTS: Reliability estimates (Cronbach's a) ranged from 0.72 to 0.94. Factor loadings in all 3 studies supported the 6-factor structure (size/symmetry, supplement use, exercise dependence, pharmacological use, dietary behavior, and physique protection). Much of the scale validation was focused on construct validity, however, correlations with the MDI's subscales and the Training Dependency subscale of the Bodybuilding Dependence Scale and the Drive for Thinness subscale of the Eating Disorder Inventory provided evidence of convergent validity also. CONCLUSIONS: From these preliminary results, the MDI appears to contribute to the identification of a newly formed disorder by offering a multi-dimensional measure of factors related to Muscle Dysmorphia.